Development of Web-Based Goods Stock Recording System Design: A Case Study In Indonesia - Eko Ragil; Resista Vikaliana; Irwansyah Irwansyah (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2025)
In this day and age, technology is something that everyone uses in their daily activities. Web system technology has been widely used. Technology is a tool that can make it easier for users to carry out daily activities. Web System technology is one of the most active technologies in all companies. Pt Ingress Technologies Indonesia still uses the old method of using stock management using Microsoft Excel. This study aims to determine the stock of goods at PT Ingress Technologies Indonesia through the Web System. This research method uses a qualitative descriptive type of research used in this study to obtain an in-depth and comprehensive development of the inventory management record system at PT Ingress Technologies Indonesia. The results of this study are the recording system through the web system is very influential for an organization or company in their management, and in inputting data it is easier when using the web. The development of a recording system that will be carried out by the company through a web system must be realized immediately, in order to increase the effectiveness and efficiency of each employee in carrying out the recording system.